Weeping and tears in Luke’s Gospel narratives: between ancient and modern commentators - Mak, SA (2024)
Within the Synoptic Gospels, Luke’s Jesus is known to be the most self-restrained. However, Luke’s is the only Gospel that describes Jesus with the verb κλαίω (it is δακρύω in John 11:35) when he weeps over Jerusalem (Luke 19:41). The Third Gospel also accounts for the greatest number of references to weeping in the NT—11 out of 40. Apart from Jesus’ weeping, there are five stories with weeping narrative characters—the widow at Nain (7:13); the anointing woman (7:38, 44); Jairus (8:52); Peter (22:62); and the daughters of Jerusalem (23:28). Luke’s is also the only Gospel to use the word ‘tear’ (δάκρυον, 7:38, 44). Luke seems to display a special interest in weeping and tears—a topic seldom discussed in Lukan studies.